2018
DOI: 10.1002/slct.201800488
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamic Acid‐Catalyzed One‐Pot Synthesis of a New Series of Biologically Relevant Indole‐Uracil Molecular Hybrids in Water at Room Temperature

Abstract: A simple, straightforward, and highly efficient three-component one-pot synthesis of a new series of biologically-interesting diverse and functionalized 5-((1H-indol-3-yl)(aryl)methyl)-6-aminopyrimidine-2,4(1H,3H)-dione derivatives has been elaborated based on molecular hybridization approach. The target molecules have been rationalized via tandem reaction of 6-aminouracils, substituted aromatic aldehydes and indoles in the presence of sulfamic acid as a low-cost and eco-friendly organocatalyst in water at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Additionally, the presence of OH groups is crucial for exhibiting favorable antimicrobial activity through intramolecular hydrogen bonding. An extensive literature survey 16 revealed that various ways have been presented for synthesizing biscoumarins from aldehyde and coumarin substrates under different conditions using a range of catalysts, including CAN, 17 taurine, 18 Fe 3 O 4 @SiO 2 @VB 1 -Ni(II), 19 N -methylpyrrolidoniumzinc chloride, 20 ethane-1,2-diol, 21 o -benzenedisulfonimide, 22 visible light, 23 BiVO 4 -NPs, 24 starch–sulfuric acid, 25 Fe 3 O 4 @SiO 2 @Ni–Zn–Fe LDH, 26 DES, 27 and many more 28 29 30 . Although current approaches have their benefits, they also have several drawbacks such as severe reaction conditions, extended reaction durations, the requirement for costly and harmful solvents, metal catalysts, and extensive purification and workup procedures.…”
Section: Table 1 Antioxidant Potential Of ...mentioning
confidence: 99%
“…Additionally, the presence of OH groups is crucial for exhibiting favorable antimicrobial activity through intramolecular hydrogen bonding. An extensive literature survey 16 revealed that various ways have been presented for synthesizing biscoumarins from aldehyde and coumarin substrates under different conditions using a range of catalysts, including CAN, 17 taurine, 18 Fe 3 O 4 @SiO 2 @VB 1 -Ni(II), 19 N -methylpyrrolidoniumzinc chloride, 20 ethane-1,2-diol, 21 o -benzenedisulfonimide, 22 visible light, 23 BiVO 4 -NPs, 24 starch–sulfuric acid, 25 Fe 3 O 4 @SiO 2 @Ni–Zn–Fe LDH, 26 DES, 27 and many more 28 29 30 . Although current approaches have their benefits, they also have several drawbacks such as severe reaction conditions, extended reaction durations, the requirement for costly and harmful solvents, metal catalysts, and extensive purification and workup procedures.…”
Section: Table 1 Antioxidant Potential Of ...mentioning
confidence: 99%
“…Sulfamic Acid-Catalyzed One-Pot Synthesis of a New Series of Biologically Relevant Indole-Uracil Molecular Hybrids. 95 Parvin and his team one-pot three-component reaction of 2-hydroxynaphthalene-1,4-dione (32), 6amino-1,3-dimethyluracil (2), and aldehydes (1) under reflux has been elaborated based on molecular iodine as a catalyst due to the rapid access to the biological activity of aminouracil-tethered trisubstituted methanes (70) (Scheme 44). 96 In following, under the same reaction conditions, they could be synthesized of aminouracil-tethered tri-substituted methane derivatives (75) via the four-component reaction of 2hydroxynaphthalene-1,4-dione (32), o-phenylenediamine (76), aldehydes (1), and aminouracil derivatives (2).…”
Section: Synthesis Of 6-aminouracil Arylmethane Derivativesmentioning
confidence: 99%
“…Zhang et al 73 reported that the reaction of aminouracil derivatives 3a and 6 with 4-methylbenzaldehyde ( 21) and 1-methyl-4-(2-nitrovinyl)benzene (22) using a recoverable carbonaceous acid (C-SO3H) as a green catalyst afforded the substituted aminopyrimidin-2,4 diones 23a and 23b rather than the expected pyrido [2,3-d] Brahmachari et al 74 developed a convenient green method for the preparation of 5-((indol-3-yl) (aryl)methyl)-6-aminopyrimidinediones 24a-w through a multi-component reaction of aryl aldehydes 21 with 6-aminouracil derivatives 3 and 6 and indoles 25 under acidic condition (Scheme 11, Table 1). A series of substituted 6-amino-5-((4-hydroxy-2-oxo-2H-chromen-3-yl)(aryl)methyl)pyrimidine-2,4-(1H,3H)-diones 28a-t was synthesized via a one-pot reaction of aryl aldehydes 21, 4-hydroxycoumarin (27), and 6-aminouracil derivatives 3 using sulfamic acid as an eco-friendly solid acid-catalyst in aqueous ethanol and under ultrasound irradiation as a green synthetic protocol (Scheme 12, Table 2).…”
Section: C-alkylation Reactionmentioning
confidence: 99%